The Reference Framework to implement Smart Healthy Age-Friendly Environments - van Staalduinen, Willeke; Dantas, Carina; Cabrita, Miriam; Ventura, Filipa; Roseiro, Pedro; Chorbev, Ivan (Magyar Gerontológia, 2024)
The concept of Smart Healthy Age-Friendly Environments (SHAFE) was born in Portugal and The Netherlands in 2017 as a Thematic Network approved by the European Commission with the support of 160 European organisations and networks. A decade earlier, the World Health Organization (WHO) launched a guide on the concept of age-friendly cities and communities to meet the challenges of ageing and urbanisation.